Fertility risk factors causing breast cancer - F Kashfi; A Nikoofar; R Mohammadi (JRI, 2002)
Next to lung cancer, breast cancer is the second cause of mortality among women. Although the prevalence of this disease has been increased, but the rate of mortality has not been changed during last three decades, this may be due to early diagnosis at the first stage of disease. The aim of this study is to determine fertility risk factor of breast cancel in women. This research is a case-control study which was performed in 1999 on three educational treatment centers related to Ministry of Health and Medical Education in Tehran. Personal, fertile characteristics in women with breast cancer were determined and compared with control group. 120 patients with breast cancer were selected randomly and compared with 120 healthy women. Results showed that majority (70%) of women with breast cancer were between 35 to 54 years old and there was significant relation between marital status and breast cancer (P<0.006). There was no relation between cancer and age of first menstruation, marriage age, number of pregnancy, age of first and last pregnancy, history of multiple pregnancy, history of breast feeding, duration of using OCP and age of menopause. But there was significant relation between number of abortion (P<0.046). In this study, risk factors of breast cancer were marital status, and there was a weak relation between number of abortion and breast cancer. Unfortunately some of this factors are not preventable, but for those factors which are manageable, proper program should be provided in order to make people aware of risk factors and ways of their prevention.
Keywords: Breast cancer, Fertility factors, Risk factor